2005
DOI: 10.1051/gse:2005007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of emotional reactivity in sheep: effects of the genotypes of the lambs and of their dams

Abstract: -A total of 1347 weaned lambs from eight genotypes were tested over five consecutive years: Romanov (ROM) and Lacaune (LAC) pure breeds, the two F1 crossbreeds (RL and LR) and the offspring of ewes from these four genotypes sired with Berrichon-du-Cher rams (BCF). The lambs were individually exposed to three challenging tests involving novelty, human contact and social isolation. Ten synthetic variables were used to express social reactivity (i.e., active vs. passive strategy), exploratory activity and reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 23 publications
3
35
0
5
Order By: Relevance
“…Nas ovelhas criadas em Bagé, foram maiores os valores de frequência cardíaca e frequência respiratória, enquanto nas ovelhas criadas na propriedade de Pedro Osório foi observado o maior valor de temperatura corporal. Os maiores valores observados em Bagé em relação às demais propriedades permitem associar o aumento desses parâmetros fisiológicos, normalmente associados à presença de vocalizações, à maior agitação, ao medo, à angústia e à emoção intensa dos animais nessa propriedade (Romeyer & Bouissou, 1992;Murphy et al, 1998;Boissy et al, 2005;Reefmann et al, 2009).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Nas ovelhas criadas em Bagé, foram maiores os valores de frequência cardíaca e frequência respiratória, enquanto nas ovelhas criadas na propriedade de Pedro Osório foi observado o maior valor de temperatura corporal. Os maiores valores observados em Bagé em relação às demais propriedades permitem associar o aumento desses parâmetros fisiológicos, normalmente associados à presença de vocalizações, à maior agitação, ao medo, à angústia e à emoção intensa dos animais nessa propriedade (Romeyer & Bouissou, 1992;Murphy et al, 1998;Boissy et al, 2005;Reefmann et al, 2009).…”
Section: Resultsunclassified
“…Todavia, não se tem explicação para a ausência de efeito do escore de comportamento materno sobre frequência respiratória e temperatura corporal, visto que normalmente essas medidas são positivamente correlacionadas, já que os testes aplicados apresentam-se associados às reações de medo, angústia, emoção intensa e agitação nos animais (Romeyer & Bouissou, 1992;Murphy et al, 1998;Boissy et al, 2005;Reefmann et al, 2009). No presente estudo, os parâmetros fisiológicos foram positiva e moderadamente correlacionados: frequência cardíaca × temperatura corporal (r = 0,35; P<0,0001), frequência cardíaca × frequência respiratória (r = 0,56; P<0,0001), apesar de a temperatura corporal × frequência respiratória (r = 0,17; P = 0,0225) apresentarem correlação positiva e fraca.…”
Section: Resultsunclassified
“…A partir da tabela 3, observa-se que as correlações entre VOC, MOV e TEN foram signifi cativas e positivas, apresentando coefi cientes moderados aos 30 e 60 dias de idade e altos aos 90 dias de idade, corroborando resultados que mostram que, em isolamento e em situações de estresse, os ovinos apresentam maior atividade locomotora, acompanhada por maior frequência de vocalização, sendo os balidos emitidos principalmente de alta intensidade (BOISSY et al, 2005). A combinação entre maiores frequências de movimentação, tensão e vocalização é geralmente expressa em situações de estresse, como durante a separação de coespecífi cos, conforme sugerido por LIGOUT et al (2011).…”
Section: Resultsunclassified
“…Breed differences in fearfulness and reactivity to humans have been demonstrated experimentally (Romeyer and Bouissou, 1992;Le Neindre et al, 1993;Viérin and Bouissou, 2003). Le Neindre et al (1993) reported variation between breeds in ease of movement through facilities, and differences in reaction style to stressors have also been described (Boissy et al, 2005). Shedding 'hair' breeds such as the Dorper and Damara have grown in popularity over the last 15 years due to reduced labour requirements compared with more traditional breeds such as the Merino (Almeida et al, 2013;Alemseged and Hacker, 2014), and quantitative differences in avoidance behaviours between Dorpers and Merinos have been found (Njisane and Muchenje, 2013).…”
Section: Sheep Factorsmentioning
confidence: 99%
“…It is also understood that many other factors, including breed, age, sex and rearing conditions, may contribute to animal behaviour during handling, although traditionally these factors have been assessed in isolation under experimental conditions (Romeyer and Bouissou, 1992;Viérin and Bouissou, 2003;Boissy et al, 2005). The use of traditional quantitative approaches to understand this social phenomenon was deemed unlikely to be adequate as there are no previous studies in this area, so a qualitative approach was used.…”
Section: Introductionmentioning
confidence: 99%